Limb apraxia profiles in different clinical samples. Issue 1 (2nd January 2020) - Buchmann, Ilka; Dangel, Mareike; Finkel, Lisa; Jung, Rebecca; Makhkamova, Inara; Binder, Andreas; Dettmers, Christian; Herrmann, Laura; Liepert, Joachim; Möller, Jens Carsten; Richter, Gabriel; Vogler, Tobias; et al.
Abstract: Objective : Limb apraxia is a motor cognitive disorder that has been mainly studied in patients with dementia or left hemisphere stroke (LHS). However, limb apraxia has also been reported in patients with right hemisphere stroke (RHS), multiple sclerosis (MS) or traumatic brain injury (TBI). This study's aim was to report detailed praxis performance profiles in samples suffering from these different neurological disorders by use of the Diagnostic Instrument for Limb Apraxia (DILA-S). Method : 44 LHS patients, 36 RHS patients, 27 patients with dementia, 26 MS and 44 TBI patients participated. The diagnostics included the imitation of meaningless and meaningful hand gestures, pantomime of tool-use, single real tool-use as well as a multistep naturalistic action task (preparing breakfast). Results : Apraxia occurred in all tested samples but to a varying degree and with dissimilar profiles. LHS patients demonstrated most severe deficits in pantomime, but they were also vulnerable to deficits in real tool-use. Dementia patients showed high incidence rates of apraxia in almost all subscales of the DILA-S. RHS patients demonstrated difficulties in imitation and pantomime of tool-use, but they did not show severe difficulties with real tool-use. TBI patients appeared challenged by multistep naturalistic actions. The tested MS sample did not show clinically relevant symptoms in the DILA-S. Conclusion : Different types of patients display varying limb apraxic symptoms detectable by the DILA-S. In these limb apraxia susceptible populations, testing should be warranted as standard. Prospectively, individual error profiles may be helpful for shaping motor cognitive training.